Factors influencing college students’ willingness to continue learning in internationalization at home - Chen Lv; Mei Li; Junjie Ma; Junsong Wang (Cogent Education, 2024)
AbstractIn recent years, due to the impact of COVID-19 and the continuous improvement of the internationalization level of university education, students’ demand for internationalized learning has been increasing, and Internationalization at Home (IaH), has become a topic of concern. However, internationalization learning is a long-term process that requires students to maintain a strong willingness to learn over a long period of time, existing literature has not yet studied the factors that affect students’ willingness to continue learning in IaH. This paper explores the factors that affect students’ willingness to continue learning in IaH by constructing a theoretical model combining Expectation Confirmation Model and Flow Theory, so as to develop a student-centered internationalized learning model that benefits the students and promotes the development of IaH. It is found that teaching resources, teaching organizers, teaching activities, teaching technology and teaching evaluation positively influence students’ willingness to continue learning, and it is also found that the flow experience has a positive influence in IaH's willingness to continue learning. This paper contributes to IaH literature by identifying factors influencing IaH students’ learning intentions and combines Flow Theory and Expectation Confirmation Model to construct an innovative theoretical model.